Wakaf Tunai, Implementasinya dalam Sistem Perbankan Syariah di Indonesia - Achmad Noer Maulidi (Institut Agama Islam Negeri Madura, 2017)
The potential of Waqaf that comes from the donation of the Community, or so-called Waqaf of money. This type of Waqaf opens great opportunities for investment business creation, whose results can be exploited in the fields of religion, education, and social services. Waqaf cash in Indonesia has not been fully socialized and has not been handled professionally. The synergy of Waqaf and sharia banking is still less united, because when sharia and waqaf banking work together it will produce a remarkable multiplier effect. From the above context, the issues studied are formulated as follows; First, what is the role of cash waqaf in Sharia Banking? Second, how is cash waqaf effect on investment? Third, how is the strategy of developing cash waqaf in Sharia Banking? The research method used is descriptive qualitative method, while the data collection procedure using bibliography, Documentation Method, Observation Method. The researcher concludes that the implementation of cash waqaf in the Islamic Banking system is still not optimal because the regulation on cash waqaf indicates that the Sharia Banking still cannot manage the cash waqaf fund is only limited to the institution in receiving Waqaf fund. While the cash waqaf securities in Investments, indicate that cash waqaf can affect the development of Investment if the cash waqaf is invested in the right field so as to increase the expected profit level. Due to the huge potentials, it is necessary to formulate several strategies to improve the development of cash waqaf especially in Sharia Banking.